Durability of Acacia Mangium and Acacia Auriculiformis against Coptotermes Sepangensis - Halimatun Saadiah Abdul Manap (2016)
Acacia mangium and Acacia auriculiformis are categorized as fast-growing trees where contribute in continuous raw materials sources for timber industries. Subterranean termite classiﬁed as the most destructive species of termites as for that Coptotermes sepangensis was used as correspondent element in this study. This research was conducted to identify the differences in durability of Acacia mangium and Acacia auriculiformis against Coptotermes sepangensis and also to determine the preferences of Coptotermes sepangensis towards dry and raw wood under choice and no choice test. Seasoning treatment of oven-drying was used in this study as comparison to raw wood sample. Result showed that Acacia auriculiformis were more durable compared to Acacia mangium. The fact reinforced by the differences in value of weight loss Acacia trees where Acacia auriculiformis show lower weight loss compared to Acacia mangium. Next, the results also showed termite preferences towards raw wood was higher compared to dry wood. The visual rating showed the preference of termite towards raw wood were more active compared to dry wood as they were increasing and dropping rate of visual rating. The analysis in durability of Acacia mangium and Acacia auriculiformis and signiﬁcant of choice and no choice test under independent group t-test was discovered. It showed there were no signiﬁcant different between Acacia mangium and Acacia auriculiformis. As for choice and no choice test there were two different result, as for raw there was signiﬁcant difference between two tests while for dry wood no signiﬁcant difference.